SOSIALISASI ATURAN DALAM MELAKUKAN KEGIATAN OLAHRAGA DIKALANGAN LANSIA DI DESA BERIRI JARAK LOMBOK TIMUR - Quddus, Abdul (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of organizing socialization regarding understanding and applying the rules for carrying out sports activities among the elderly in Beriri Distance Village, Wanasaba District, East Lombok, the method of implementing this activity is to provide an explanation of the rules for exercise and provide knowledge on how to do sports among the elderly properly. The results of this activity are expected to be able to receive the material with enthusiasm and great willingness so that the training material can be well absorbed by all elderly people. Apart from that, the enthusiasm of the participants was very high so it could be said that this activity received a positive response from the community.